ANALISIS MERGER YANG TERJADI PADA BADAN USAHA BERBENTUK CV (Studi Kasus pada Perusahaan Distributor CV Semarang Indah dan CV Merauke Indah) - Nanda Khairun Nissa; Endang Tri Widyarti (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT CV Semarang Indah and CV Merauke Indah are distributor companies with the same core business activities and owner. Both of the companies plan to be merged and change their business entity to become PT because of inefficient administration for both companies, less focus for selling their product, and not incorporated company. Based on the regulation in Indonesia, it doesn’t have the explanation about merger in CV. In the other hand, the discussion about merger in CV is not found about their characteristic, process, and the aspect that become the feasibility of merger. To analysis the problems, the research was conducted with qualitative methods. The author uses study cases from condition of CV Semarang Indah and CV Merauke Indah by in-depth interview to the top leader and tax consultants for the primary data source. For secondary data source used annual report for both companies during 2019-2021. The results showed the characteristic and process merger in CV is not same with PT. CV doesn’t have the certain regulation therefore the process depends on its problem. The process in CV has few steps. The merger CV will stop transaction purchasing and move to the CV that receive the merger. The feasibility for both companies have already well deserved to be merged based on financial analysis with increasing their market value and also growing their average selling because of CV Semarang Indah and CV Merauke Indah decision to be merged